2015
DOI: 10.1021/ef502611d
|View full text |Cite
|
Sign up to set email alerts
|

Using Ground and Intact Coal Samples To Evaluate Hydrocarbon Fate during Supercritical CO2 Injection into Coal Beds: Effects of Particle Size and Coal Moisture

Abstract: To investigate the potential for mobilizing organic compounds from coal beds during geologic carbon dioxide (CO 2 ) storage (sequestration), a series of solvent extractions using dichloromethane (DCM) and using supercritical CO 2 (40°C and 10 MPa) were conducted on a set of coal samples collected from Louisiana and Ohio. The coal samples studied range in rank from lignite A to high volatile A bituminous, and were characterized using proximate, ultimate, organic petrography, and sorption isotherm analyses. Sorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 84 publications
2
22
0
Order By: Relevance
“…Field based demonstration sites have shown that CO2 injection leads to greater dissolved organic carbon within sedimentary brine formations (Kharaka et al, 2006a) as well as increased concentrations of BTEX, PAHs, phenols and other toxic compounds in groundwater monitoring wells (Kharaka et al, 2009, Kharaka et al, 2010a, Kharaka et al, 2010b, Scherf et al, 2011. Laboratory based experiments using both scCO2 and organic solventsconfirmed that reservoir rocks are sources of organic compounds and that the extractable organic material was dominated by n-aliphatic and aromatics (Jarboe et al., 2015, Kolak and Burruss, 2006, Kolak and Burruss, 2014, Kolak et al, 2015, Zhong et al, 2014a, Zhong et al, 2014b. In particular, nalkanes ranging from n-C9 to n-C31 have been identified and have over 30 different aromatic compounds, including BTEX and naphthalene (Jarboe et al., 2015, Kolak and Burruss, 2014, Kolak et al, 2015, Zhong et al, 2014b.…”
Section: Reservoir As a Source Of Other Relevant Gases And Inorganic mentioning
confidence: 99%
See 1 more Smart Citation
“…Field based demonstration sites have shown that CO2 injection leads to greater dissolved organic carbon within sedimentary brine formations (Kharaka et al, 2006a) as well as increased concentrations of BTEX, PAHs, phenols and other toxic compounds in groundwater monitoring wells (Kharaka et al, 2009, Kharaka et al, 2010a, Kharaka et al, 2010b, Scherf et al, 2011. Laboratory based experiments using both scCO2 and organic solventsconfirmed that reservoir rocks are sources of organic compounds and that the extractable organic material was dominated by n-aliphatic and aromatics (Jarboe et al., 2015, Kolak and Burruss, 2006, Kolak and Burruss, 2014, Kolak et al, 2015, Zhong et al, 2014a, Zhong et al, 2014b. In particular, nalkanes ranging from n-C9 to n-C31 have been identified and have over 30 different aromatic compounds, including BTEX and naphthalene (Jarboe et al., 2015, Kolak and Burruss, 2014, Kolak et al, 2015, Zhong et al, 2014b.…”
Section: Reservoir As a Source Of Other Relevant Gases And Inorganic mentioning
confidence: 99%
“…Laboratory based experiments using both scCO2 and organic solventsconfirmed that reservoir rocks are sources of organic compounds and that the extractable organic material was dominated by n-aliphatic and aromatics (Jarboe et al., 2015, Kolak and Burruss, 2006, Kolak and Burruss, 2014, Kolak et al, 2015, Zhong et al, 2014a, Zhong et al, 2014b. In particular, nalkanes ranging from n-C9 to n-C31 have been identified and have over 30 different aromatic compounds, including BTEX and naphthalene (Jarboe et al., 2015, Kolak and Burruss, 2014, Kolak et al, 2015, Zhong et al, 2014b. These laboratory based studies have also shown that the amount and type of extractable organic compounds was influenced by the solvent type (e.g., scCO2 vs. dichloromethane), exposure duration, and the temperature and pressure of the extraction conditions as well as the source rock, water content, and geologic setting.…”
Section: Reservoir As a Source Of Other Relevant Gases And Inorganic mentioning
confidence: 99%
“…The data also show that the porosity of the treated intact and tectonic coal samples increased by 18.90% (from 4.18% to 4.97%) and 23.14% (from 5.23% to 6.44%), respectively. Previous studies [22,23,41] showed that ScCO2 can mobilize some of the polycyclic aromatic hydrocarbons and aliphatic hydrocarbons in the coal. Additionally, CO2 will form carbonic acid when it is dissolved in the water in the coal seams, and this acid can dissolve some of the inorganic minerals in the coal, such as calcites, dolomites, and magnesites [42].…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Additionally, ScCO 2 is an organic solvent and can mobilize some of the organic matter in the coal. If some of the CO 2 is dissolved in the reservoir water, the pH decreases and the CO 2 -enriched solution can dissolve some of the minerals present [22][23][24]. Studies also showed that CO 2 adsorption can cause the coal's matrix to swell [25].…”
Section: Introductionmentioning
confidence: 99%
“…The newly generated CO, the aliphatic and aromatic hydrocarbons, and the polycyclic aromatic hydrocarbons in the coal matrix extracted by the ScCO 2 are biologically toxic. These substances dissolved in gas and water will enter the coal seams, the rock formations, and the groundwater surrounding the coal seam and will become environmental hazards [23,68].…”
Section: Variations In Aliphatic Chain Length and Aliphatic Hydrocarbmentioning
confidence: 99%